2019
DOI: 10.1007/s10592-019-01213-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic status of the endangered plant species Gladiolus palustris in the western part of its distribution area

Abstract: Many endangered plant species suffer from the effects of ongoing fragmentation of their populations leading to a loss of genetic diversity through genetic drift. In addition, populations of rare plants may also be affected by hybridization with other plant species. We studied the genetic population structure of populations of the endangered Gladiolus palustris in the western limit of its distribution area using AFLP markers. In addition, we clarified the taxonomic status of populations where hybridization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…The resumption of mowing for conservation purposes in our study area undertaken by the DBNP authority has halted the encroachment of woody species and has avoided a drastic change in plant composition. The population size of G. palustris is remarkable in terms of flowering ramets compared to literature data (see for example the populations studied in France and Switzerland by Daco et al 2019). The mowed area shows a larger occurrence and higher density of G. palustris in terms of flowering ramets (as shown by GLM) and percentage cover (as shown by GLM and linear regression) than the non-mowed area just outside the park border.…”
Section: Discussionmentioning
confidence: 67%
“…The resumption of mowing for conservation purposes in our study area undertaken by the DBNP authority has halted the encroachment of woody species and has avoided a drastic change in plant composition. The population size of G. palustris is remarkable in terms of flowering ramets compared to literature data (see for example the populations studied in France and Switzerland by Daco et al 2019). The mowed area shows a larger occurrence and higher density of G. palustris in terms of flowering ramets (as shown by GLM) and percentage cover (as shown by GLM and linear regression) than the non-mowed area just outside the park border.…”
Section: Discussionmentioning
confidence: 67%
“…The strong differentiation of A. foemina populations between geographical regions indicates that current gene flow is very low. Daco et al ( 2019 ) analyzing the protected species of Gladiolus palustris , found that although most of the population of G. palustris in the regions retained significant genetic variation, genetic diversity is likely to decrease in small populations due to genetic drift.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive approach, including the analysis of anthropogenic and habitat impacts, allows determining the species susceptibility to population reduction and developing strategies for its protection. According to Daco et al ( 2019 ), in the case of high fragmentation of the population, in order to preserve biodiversity, the conservation of populations from each regional cluster is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, populations from two regions viz., Bathad from Kullu and Rangrik from Spiti valley revealed unique and different genetic structure, can be considered as potential populations for conservation strategy planning via introducing them to different regions to induce artificial gene flow 41 . Therefore, conservation of diverse individuals of each population is important to preserve the genetic diversity of D. hatagirea in the cold desert regions of Himachal Pradesh as diverse gene pools improves the chances of adaptation for future climatic conditions 42 .…”
Section: Methodsmentioning
confidence: 99%